Identifikasi dan Seleksi Fungi Endofit Daun Sirih Hijau (Piper betle L.) Penghasil Enzim Selulase - Dhia Salsabila Hakim; Rina Sri Kasiamdari (Berkala Ilmiah Biologi, 2023)
Abstract: Endophytic fungi were known in bioethanol industries due to their role in secreting secondary metabolites in the form of cellulolytic enzymes, which were known to be superior to bacteria. The secretion of metabolic enzymes depended on the host they invaded. Herbal plants were recognized as habitats for various endophytic fungi. Betel leaf (Piper betle L.) was one such herbal plant known for its high metabolite content. The aim of this study was to identify endophytic fungi living on betel leaf, conduct cellulolytic tests on the identified fungi, and determine which fungi exhibited the highest cellulolytic activity. The study yielded three species of endophytic fungi from betel leaf: Fusarium graminearum, Fusarium oxysporum, and Colletotrichum coccodes. All three samples showed positive results, producing cellulase enzymes characterized by the presence of a clear zone around the colonies. F. oxysporum was identified as the highest producer of cellulase enzymes, with a concentration of 0,033 U/ml.